2004
DOI: 10.1002/jcb.20343
|View full text |Cite
|
Sign up to set email alerts
|

Developmental regulation and cellular distribution of human cytosolic malate dehydrogenase (MDH1)

Abstract: Human cyotsolic malate dehydrogenase (MDH1) is important in transporting NADH equivalents across the mitochondrial membrane, controlling tricarboxylic acid (TCA) cycle pool size and providing contractile function. Cellular localization studies indicate that MDH1 mRNA expression has a strong tissue-specific distribution, being expressed primarily in cardiac and skeletal muscle and in the brain, at intermediate levels in the spleen, kidney, intestine, liver, and testes and at low levels in lung and bone marrow. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 40 publications
3
41
0
Order By: Relevance
“…Cytosolic oxaloacetate is then converted to malate by MDH1, and acetyl-CoA is used for fatty acid synthesis. In mammals, MDH1 is highly expressed in many tissues, and its different roles are determined by its expression levels (15)(16)(17).…”
Section: Construction Of Retroviral Vectors and Transductionmentioning
confidence: 99%
“…Cytosolic oxaloacetate is then converted to malate by MDH1, and acetyl-CoA is used for fatty acid synthesis. In mammals, MDH1 is highly expressed in many tissues, and its different roles are determined by its expression levels (15)(16)(17).…”
Section: Construction Of Retroviral Vectors and Transductionmentioning
confidence: 99%
“…All proteins had been previously linked to malignancies and are involved in cellular processes like cell growth (RING finger protein and protein kinase C), regulation of the biological homeostasis including haematopoiesis and immunity (G-protein-coupled receptors), apoptosis (VCP) and processes related to cell division (Malate dehydrogenase). 9,11,[33][34][35] Since quantitative 2-DE was not performed, our results only indicate that these proteins are more frequently present in the average proteome of one responder group. This does not exclude that the respective protein will not be expressed in patients belonging to the other responder group, because proteins with a low expression level, for example, might accidentally escape software recognition.…”
Section: Discussionmentioning
confidence: 80%
“…Both MDH1 and MDH2 expression levels in lung and spleen are low compared to liver. The lowest level of MDH1 expression was observed in human lung and bone marrow (Lo et al, 2005).…”
Section: Discussionmentioning
confidence: 91%
“…In humans, MDH1 mRNA is expressed at relatively high levels in heart, skeletal muscle and brain (Lo et al, 2005). Similarly, Mori et al (2009) reported that MDH1 mRNA is highly expressed in skeletal muscle in cats.…”
Section: Discussionmentioning
confidence: 92%